THE 16S rRNA GENE MARKER-BASED MOLECULAR IDENTIFICATION OF CULTURABLE COLIFORM BACTERIA ISOLATED FROM FORAMINIFERA CALCARINA DERIVED FROM PRAMUKA ISLAND WATERS, THE SERIBU ISLAND DISTRICT, JAKARTA PROVINCE - Agung, Mochamad Untung Kurnia -; Askar, Agus Tri; Andriani, Yuli; Yuliadi, Lintang Permatasari (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2020)
Contamination of coliform bacteria in benthic foraminifera has been reported due to pollution of organic wastes in the aquatic environment around coral reef ecosystems and this event was known to interfere the process of foraminifera shell formation which in turn resulted the disruption of the role of foraminifera in the process of formation of coral reef bottom sediments. The aim of this research is to identify the isolates of culturable coliform bacteria that contaminate foraminifera Calcarina species isolated from the waters of the Pramuka Island, the Seribu Island district, Jakarta Province using the 16S rRNA gene markers. Foraminifera sampling was carried out in the waters of Pramuka Island, the Seribu Island district, Jakarta Province in 5 (five) stations, while the process of bacterial isolation and molecular identification were carried out at the Laboratory of Microbiology and Molecular Biotechnology (MICROMOL), Faculty of Fisheries and Marine Sciences (FPIK), University Padjadjaran. Molecular identification was carried out using the Polymerase Chain Reaction (PCR) method based on the 16S rRNA gene markers. Sequencing is done by sending PCR results to 1st Base, sequencing service company, in Singapore and then, the aligning of sequencing results with databases in genBank was done using the Basic Local Alignment Search Tool (BLASTTM) program available on the National Center for Biotechnology Information (NCBI) website. The results of 16S rRNA gene amplification from the five isolates produced amplicons of ± 1400 bp length with concentrations ranging from 157.5 µg / mL-230 µg / mL and with a purity ratio ranging from 1.477-1.769. While the results of BLAST and phylogenetic analysis showed that the five isolates were closely related to the isolate Eschericia coli strain inspire99 (Acc No. JQ315935.1), which was isolated from the waters of the Bay of Bengal, India. These results also indicate the existence of ecological connectivity between the waters of the Bay of Bengal in India and the waters of Pramuka Island in Indonesia.